(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article gives general information about the main directions of Corpus linguistics and important features of it. In addition, it provides several notions from famous linguists namely V.P. Zakharov, T. McEnery, E. Finegan, M. McCarthy and etc as well as they identified main distinctive charactersitics of Corpus Linguistics.